Effects of land‐use change on functional and taxonomic diversity of Neotropical bats. (3rd December 2019) - Farneda, Fábio Z.; Meyer, Christoph F. J.; Grelle, Carlos E. V.
Abstract: Human land‐use changes are particularly extensive in tropical regions, representing one of the greatest threats to terrestrial biodiversity and a key research topic in conservation. However, studies considering the effects of different types of anthropogenic disturbance on the functional dimension of biodiversity in human‐modified landscapes are rare. Here, we obtained data through an extensive review of peer‐reviewed articles and compared 30 Neotropical bat assemblages in well‐preserved primary forest and four different human‐disturbed habitats in terms of their functional and taxonomic diversity. We found that disturbed habitats that are structurally less similar to primary forest (pasture, cropland, and early‐stage secondary forest) were characterized by a lower functional and taxonomic diversity, as well as community‐level functional uniqueness. These habitats generally retained fewer species that perform different ecological functions compared to higher‐quality landscape matrices, such as agroforestry. According to functional trait composition, different bat ensembles respond differently to landscape change, negatively affecting mainly gleaning insectivorous bats in pasture, narrow‐range species in cropland, and heavier animalivorous bats in secondary forest. Although our results highlight the importance of higher‐quality matrix habitats to support elevated functional and taxonomic bat diversity, the conservation of bat species that perform different ecological functions in the mosaic of human‐modified habitats also depends on the irreplaceable conservation value of well‐preserved primary forests. Our study based on a pooled analysis of individual studies provides novel insights into the effects of different human‐modified habitats on Neotropical bat assemblages. Abstrata: Mudanças no uso da terra gerada pelos humanos são particularmente extensas nas regiões tropicais, representando uma das maiores ameaças à biodiversidade terrestre e um importante tópico de pesquisa em conservação. No entanto, são raros os estudos considerando os efeitos de diferentes tipos de distúrbios antropogênicos sobre a dimensão funcional da biodiversidade em paisagens modificadas pelos humanos. Aqui, obtivemos dados através de uma extensa revisão de artigos revisados ​​por pares e comparamos a diversidade funcional e taxonômica de 30 comunidades de morcegos Neotropicais em florestas primárias bem preservadas, e em quatro diferentes habitats alterados pelos humanos. Descobrimos que habitats perturbados que são estruturalmente menos semelhantes à floresta primária (pastagem, terras cultiváveis e floresta secundária em estágio inicial de regeneração) foram caracterizados por uma menor diversidade funcional e taxonômica, bem como por uma menor originalidade funcional das comunidades. Tais habitats geralmente apresentam menos espécies que desempenham diferentes funções ecológicas em comparação com matrizes de maior qualidade, como a agrofloresta. De acordo com a composição das características funcionais, diferentes conjuntos de morcegos respondem diferentemente à mudança da paisagem, afetando negativamente principalmente os morcegos insetívoros na pastagem, espécies com reduzida área de vida nas terras de cultivo e os morcegos animalívoros de maior peso corporal na floresta secundária. Embora nossos resultados destaquem a importância de habitats com matrizes de alta qualidade para manter a diversidade funcional e taxonômica de morcegos, a conservação de espécies de morcegos que desempenham diferentes funções ecológicas no mosaico de habitats modificados pelos humanos também depende do valor insubstituível de conservação de florestas primárias bem preservadas. Nosso estudo, baseado em uma análise conjunta de estudos individuais, fornece novos entendimentos sobre os efeitos de diferentes habitats modificados pelos humanos sobre as comunidades de morcegos Neotropicais.